PENGARUH PEMBERIAN DOLOMIT TERHADAP BEBERAPA SIFAT KIMIA TANAH GAMBUT DAN PERTUMBUHAN SERTA HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L) - Farah Ilham; Teguh Budi Prasetyo; Sandra Prima (Jurnal Solum, 2019)
This research was aimed to study the effect of dolomite on chemical properties of peat soil and as well as on growth and yield of onion. The research was in form of pot experiment having 5 treatments (0 ton dolomite Ha-1 ; 2.5 ton dolomite Ha-1 ; 5 ton dolomite Ha-1 ; 7.5 ton dolomite Ha-1 ; 10 ton dolomite Ha-1) and 3 replications which were allocated in Completely Randomized Design. Parameters analyzed were pH H2O, available sulphur, available phosphorus, CEC, and exchangeable cations, as well plant height, plant dry weight, sulphur uptake, and diameter of tubers. Data resulted were analyzed the variance using F-test at 5% level of significance and then it was continued using Duncan New’s Multiple Range Test (DNMRT) at 5% level if F-test > F-table. The results showed that 10 ton dolomite Ha-1was the optimum dose to improve chemical characteristics of peat soils. It increased pH H2O by 1.16 unit, sulphur uptake by 0.005 %, available phosphorus by 5.7 ppm, CEC by 9.67 Cmol Kg-1 and exchangeable K by 0.09 Cmol Kg-1, Mg by 0.19 Cmol Kg-1, Ca by 0.31 Cmol Kg-1 compared to soil without treatment ( 0 ton Ha-1 ). It also increased production of onion, especially plant height by 22.63 cm, plant fresh weight by 43.14 g and dry weight by 2.89 g, tuber fresh weight by 21.92 g, and dry weight by 2.89 g, sulphur uptake by 0.03 %, and diameter of tubers from none to be 2.00 cm compared to soil without treatment.Key words : dolomite, peat soils, onion, soil chemical characteristics